Formação de formadores: implementação de uma política de formação de coordenadores pedagógicos realizada por uma diretoria de ensino da rede pública da Grande São Paulo - Correa, Adriano Borba (2021)
The focus of this research is to analyze the implementation of the training policy for coordinators, in the meetings called “Work Meeting with Coordinating Teachers”, held by the Pedagogical Nucleus of the Teaching Directorate, its implications and consequences in the process of continuous training of the “Work Lessons Collective Pedagogical” (ATPCs), in a school unit belonging to the jurisdiction of the Greater São Paulo Board of Education. The aim of this research is to highlight the process of building the proposal for the formation of the PCNPs of the Pedagogical Nucleus of the Teaching Directorate. The research was carried out within the scope of educational sociology studies, with the intention of analyzing the school-centered training process constituted by the subjects participating in this formative process, the PCNPs and the PCs, in the light of the activity concept proposed by Vygotsky and Engeström; of the critical perspective of training, development and construction of the professional identity of teachers and teacher trainers, according to Imbernón, Marcelo García, Barroso and Huberman; as well as of the concepts of school cultures, teacher culture and managers culture proposed by Viñao Frago. The hypothesis that guides the research is linked to the idea that such a continuous training initiative carried out by DE, in meetings with the coordinating teachers, has as its core aligning the pedagogical guidelines of the DE and the school units, with the training of the CP / trainers of teachers, during the process of teacher training in the ATPCs of the schools where the CP / trainers work. The data obtained, through document analysis, monitoring and observation of meetings for training coordinators and ATPCs in schools, for teacher training and semi-structured interviews with 2 PCNPs and 1 PC, were organized in summary tables and tables. The results suggest that the formative proposal characterizes by evidencing the formatting of the trainers, legitimizing a public policy of replicability, reproduction and multiplication of processes and procedures, plastering the subjects during the formative itinerary, limiting the professional development process of the subjects, to the mere realization of developments of formations prescribed by Seduc-SP